ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP NASABAH YANG MENGGUNAKAN SUATU PRODUK BANK BERDASARKAN INFORMASI ATAS IKLAN PRODUK BANK MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - MARTINA JULIANCE PB. SIHOMBING (PREMISE LAW JURNAL, 2016)
Bank Indonesia as the Central Bank that functions to control every banking business activity related to the activities of promoting/offering the bank products, issued the regulation of Bank Indonesia No.7/6/PBI/2005 on Transparent Information of Bank Product and the Use of Customer’s Personal Data. Every bank that domiciles in Indonesia is required to subject to the Regulation. In Advertising their products, the banks are not allowed to include information or explanation about the characteristics of the bank product whose shape or location is hard to understand. The information containing misleading elements can inflict loss to the customers in their capacity as customers that a legal protection is needed for them in the implementation of the activity of information about the bank product advertisement that contains misleading elements based on Law no. 8/1999 on Consumer Protection. This legal protection for customer is reviewed based on the position of rights and obligations of the parties involved in accordance with Article 4 of Law No. 8/1999 on Consumer Protection.Disputes arising from the implementation of the information about the advertisement of bank products can be settled throught several legal actions on dispute settlement in the provisions of the Regulation of Bank Indonesia (PBI) No.7/7/2005 on Customer Complaint Settlement done in peace and banking mediation banking. Furthermore, the implementation of dispute settlement can be done throught litigation (court) and out of court. Keywords : advertising, Bank Product, Legal Protection